Growth and Development of Entrepreneurship in Renewable Energy Sector of Nepal - Yadav, Maheshwar Prasad (International Research Journal of MMC, 2022)
This paper assesses the growth and development of entrepreneurship in a renewable energy sector of Nepal. The study adopts descriptive cum analytical research design. The required secondary data covering a period of 42 years of biogas sector, 25 years of solar sector, and 55 years of micro-hydro sector leading to a total of 122 observations were collected. They were related to energy mix, number of households, number of renewable energy systems installations, and renewable energy enterprises (REEs) for this study. This study has adopted percentage changes over the period, structure, pattern, and trends by development regions and periodic development plans for analyzing the data. The results show that manifold increase from 1992/93 to 2016/17 though the growth has slowed down in recent years. The results indicated that with the increase in GDP, population and number of households, there was an increase in the number of REEs, biogas companies, solar companies and micro-hydro construction companiesIn addition, the results on number and capacity of renewable energy systems installed by development regions and by periodic development plans showed that the growth and development of renewable energy sector was encouraging throughout the country and over the period. This study is useful for renewable energy enterprises (REEs), development actors in the sector, academia, and policy makers. The study can be extended by incorporating other sectors of renewable energy such as, improved cooking stove, wind technology and biomass sectors to get greater insight into the results.